Evaluation of screening of neonatal sepsis - R., Kartik; Manjunath, Sahana; Doddabasappa, Prathiba; J., Malavika (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal sepsis is an important cause of neonatal mortality and morbidity. Early diagnosis of sepsis is difficult due to its non- specific clinical presentation. The gold standard for diagnosis is blood culture, which is obtained in only 25%-40% of cases and requires 48-72 hours. There is a need for a sepsis screen for early diagnosis of septicemia and identification of culture negative cases. The objective of the study was to study the role of sepsis for early diagnosis of septicaemia and identification of culture negative cases and to compare the rapid diagnostic tests with blood culture singly and in combinations for specificity and sensitivity. Methods: 60 cases of suspected septicemia were studied. Total leucocyte count, bandforms peripheral smear examination, C-reactive protein assay, micro-ESR, and blood culture study was investigated. Results: Study revealed that CRP had maximum sensitivity while band neutrophil ratio had balanced sensitivity and specificity. In the two tests, CRP with PS/BF had balanced sensitivity and specificity. In the three tests combination, CRP with TC with micro-ESR had balanced sensitivity and specificity in proven sepsis, While CRP with BF with micro-ESR had balanced sensitivity and specificity in most probable sepsis cases. Conclusions: Neonatal sepsis has vague signs and symptoms, so high index of suspicion helps in arriving early diagnosis and management. CRP had maximum sensitivity in the individual tests. Using either two tests (CRP + PS/BF) or three tests (CRP + Micro ESR + BF/TC) most of the sepsis cases could be identified and sepsis negative cases can be ruled out. Sepsis screen is helpful in avoiding overuse of antibiotics.